Au@ZnO core–shell nanostructures with plasmon-induced visible-light photocatalytic and photoelectrochemical properties. Issue 7 (29th April 2016) - Shao, Xiankun; Li, Benxia; Zhang, Baoshan; Shao, Liangzhi; Wu, Yongmeng
Abstract : Au@ZnO core–shell nanostructures exhibit enhanced photocatalysis under both simulated sunlight and monochromatic LED light due to the synergistic effect between the plasmonic Au-nanosphere cores and the semiconducting ZnO shells. Abstract : Constructing a core–shell nanostructured photocatalyst by integration of plasmonic metal nanocrystals and a semiconductor can offer large active metal/semiconductor interfacial areas and avoid aggregation of the metal nanocrystals. Herein, well-defined Au@ZnO core–shell nanostructures were prepared by coating ZnO on cetyltrimethylammonium bromide (CTAB) stabilized Au nanospheres in aqueous solution. The resultant core–shell nanostructures have Au-nanosphere cores with a diameter of ∼55 nm and ZnO shells with a thickness of ∼50 nm. After calcination at 350 °C in air, the mesoporous ZnO shell with higher crystallinity and a larger surface area was obtained without any significant change in the morphology or plasmon band of Au@ZnO. The specific surface plasmon resonance of the Au-nanosphere cores endows the Au@ZnO nanostructures with strong visible light absorption around 550 nm. The photocatalytic degradation of an organic pollutant was performed under simulated sunlight and monochromatic LED light with three different wavelengths (365 nm, 520 nm, 660 nm), demonstrating the enhanced photocatalysis of the Au@ZnO nanostructures. Furthermore, the Au@ZnO as a photoelectrode material presents a higher photocurrent density than that of pure ZnO nanoparticles under simulated sunlight. The electrochemical impedance spectra (EIS) Nyquist plots also confirm the higher charge transfer efficiency of the Au@ZnO nanostructures. Such plasmonic metal–semiconductor core–shell nanostructures would provide a desirable platform for studying plasmon-induced/enhanced processes and have great potential in light-harvesting applications.